Simulation of electrical effects with respect to fine particle separation at conditions of pressurized pulverized coal combustion - van der Zwaag, T.; Haep, S.; Schmidt, K.G. (Powder technology, 2008)
Realization of the power plant concept with pressurized pulverized coal combustion (PPCC) needs a flue gas nearly free of particulate matter with respect to gas turbine life cycle. Current studies at the pilot plant of the PPCC-development project in Dorsten, Germany, show that the limit for safe turbine operation is now reached with the used multi-stage molten ash separator. The separation principle that leads to the observed improvement of fine particle separation is a subject matter of the current scientific research. Thus computational fluid dynamics (CFD)-modelling carried out at IUTA focuses on the calculation of fine particle dynamics at high temperatures. This includes modelling of particle transport due to inertia and electrophoresis as well as charging kinetics with respect to interaction of electrically charged fine particles and different ceramic collector materials at temperatures up to 1600–1700 K. Computational fluid dynamics (cfd)-simulations were carried out that focus on fine particle dynamics at high temperatures. A model was developed that includes particle transport due to electrophoresis as well as charging kinetics with respect to interaction of electrically charged fine particles and different ceramic collector materials at temperatures up to 1600–1700 K. [Display omitted]